Pengaruh Dana Pihak Ketiga, Suku Bunga Kredit Dan Produk Domestik Regional Bruto Terhadap Penyaluran Kredit Di Kalimantan Barat - B01110081, DZIKRULLAH MUHAMMAD ASHIDIQI (Jurnal Curvanomic, 2015)
The research work entitled : â€œThe effect Of Third Party Funds, Interest Rate Credit and Regional Gross Domestic Product On Distribution Of Credit In West Kalimantanâ€. The research work was aimed for finding out the effect of third party funds (DPK), interest rate credit and regional gross domestic product (PDRB) on credit distribution in West Kalimantan between 2009 and 2013. The research employed quantitative descriptive methodology using secomdary data, rime series , from Cerntral Bureau for Statistics and Bank Indonesia of West Kalimantan. The data was analyzed by using Eviews 6 Observation for 5 year data quarterly, in West Kalimantan from 2009 to 2013. According to result of multiple regression, it showed that DPK had positive and significant effect on credit in West Kalimantan. The more DPK joins banks, the more credit will be distributed. Besides, the interest rate credit did not impact positively and significantly which means that the higher interest rate credit, the lower number of credit distributions. Finally, regional gross domestic product had negative and not significant influence, which means that if PDRB increases, the ability of people fulfill their needs will also rise. Â  Key words : DPK, Interest Rate Credit, PDRB, Distribution of Credit